The third way and the challenges to economic and monetary union macropolicies - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2002)
In the United Kingdom the emergence of a New Labour has been closely associated with the development of the notion of the third way. Tony Blair, for example, stated that New Labour is neither old left nor new right. . . . Instead we offer a new way ahead, that leads from the centre but is profoundly radical in the change it promises. In a similar vein Giddens locates the third way by reference to two other ways of classical social democracy and neoliberalism. Although some notable contributions have been made on the subject of the third way, rather little has been written specifically on the economic analysis underpinning it. This paper infers such an analysis by working back from the policies and policy pronouncements of governments. To do so, the paper examines the types of economic analyses being used to underpin the ideas of the third way; the suggestion that the ideas surrounding the economic analysis of the economic and monetary union's (EMU's) theoretical and policy framework are firmly embedded in that of third way; and the argument that the challenge for EMU macropolicies lies in their potential to achieve full employment and low inflation in the euro system. On the last point, the author concludes that these policies, as they currently operate, are not very promising. Alternatives are therefore suggested.
Keywords: 330